The Vital Role Of Medical Laboratories During The Hajj Season - Abdullah Fahd Alqahtani, ‏ Saleh Ibrahim Alfurayji, ‏ Mohammed Abdulkarim Alshobash, ‏ Fahad Hulayyil Alanazi, ‏ Abdulaziz Sadun Alanazi (Migration Letters, 2020)
The Hajj, the annual Islamic pilgrimage to Mecca in Saudi Arabia, is one of the largest mass gatherings in the world, attracting millions of pilgrims from around the globe. This influx of people poses significant challenges in terms of healthcare provision, including the need for efficient and reliable medical laboratory services. This paper explores the vital role of medical laboratories in supporting the healthcare system during the Hajj season, encompassing their involvement in disease surveillance, outbreak prevention, and the m[1]anagement of pilgrims’ health. The review discusses the unique epidemiological profile of the Hajj, the common health issues faced by pilgrims, and the critical contributions of medical laboratories in addressing these challenges. The paper highlights the importance of strengthening the capacity and capabilities of medical laboratories and the need for effective coordination and collaboration among healthcare stakeholders to ensure the successful and safe execution of the Hajj pilgrimage.